Research and suggestion on the choice of the acceptance indexes of the TD-LTE VoLTE wireless network engineering - Anda DEN; Deping XU; Linjie SUN; GLujing GEN; Xinning SHI; Xiang WAVG (Dianxin kexue)
Firstly,the similarities and differences between the acceptance of the TD-LTE VoLTE wireless network engineering and other wireless network engineering were discussed.Then,referring to the different phases of engineering acceptance,the choice of indexes was analyzed.And finally,by driving tests and comparison research,the values of the index were suggested.